2013
DOI: 10.1167/iovs.12-11483
|View full text |Cite
|
Sign up to set email alerts
|

Mature Dendritic Cell Suppression by IL-1 Receptor Antagonist on Retinal Pigment Epithelium Cells

Abstract: PURPOSE. To determine whether retinal pigment epithelial (RPE) cells can inhibit mature dendritic cells (mDCs).METHODS. Cultured RPE cells were established from C57BL/6 mice. DCs were established from bone marrow cells of normal mice, and mDCc were induced by culture in medium containing granulocyte macrophage-colony-stimulating factor (GM-CSF) and IL-4 in the presence of lipopolysaccharide and TNF-a. Activation of mDCs was assessed by a proliferation assay and ELISA to measure the production of pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The finding of RPE immunomodulation has involved isolating and culturing the primary RPE cells that proliferate into a monolayer [5,7]. This is a process that is not usually seen except in wounded retinas.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of RPE immunomodulation has involved isolating and culturing the primary RPE cells that proliferate into a monolayer [5,7]. This is a process that is not usually seen except in wounded retinas.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ocular resident cells at the inner layer of the blood ocular barrier, such as the iris PE cells, ciliary body PE cells, retinal PE cells, and corneal endothelial cells, have the capacity to suppress the activation of bystander inflammatory immune cells, including the CD4 þ T helper cells. [3][4][5][6][7][8][9][10][11][12] RPE cells are the ocular resident cells that participate in the immune regulation of the posterior segment in the eye. Furthermore, RPE cells have the capacity to convert activated T cells into regulatory T (Treg) cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent studies by our own and other various laboratories have investigated the immune regulation by ocular resident cells (i.e., endothelial cells of the cornea and pigment epithelial cells of the iris, ciliary body, and retina). [3][4][5][6][7][8][9][10][11][12][13][14][15] Our research group focused on these ocular resident cells because they are located at the gate of the blood ocular barrier. Based on our current knowledge, it is obvious that immune regulation would work much more efficiently at the gate of the blood ocular barrier as opposed to after the activated CD4 þ T cells enter the eye.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have implicated IL-1 receptor (IL-1R) signaling on dendritic cell function, including in the generation of CD8 T cell responses to viruses (2224), the role of graft- or recipient-derived IL-1R signals in alloimmune T cell responses to organ allografts has not been well investigated. We hypothesized that IL-1R signaling on allograft dendritic cells would be required to provoke optimal donor alloantigen-reactive endogenous memory T cell and de novo T cell responses.…”
Section: Introductionmentioning
confidence: 99%